Kadar Lemak, Solid Non Fat, Total Padatan, dan density Susu Kambing Pasteurisasi dengan Penambahan Ekstrak Daun Ubi Jalar Ungu Pada waktu Penyimpanan yang Berbeda - Maryana, Bela; Sihite, Mikael; Triastanti, Resti Kurnia (Jurnal Teknologi Hasil Peternakan, 2024)
Goat's milk is an animal product with high fat so it is more easily spoiled. The addition of natural antioxidants to purple sweet potato leaves, potentially  to maintain pasteurized milk. The aim of this study was to determine the effect of the addition of purple sweet potato leaf extract on the chemical quality of pasteurized goat's milk at different concentrations and storage times. The study used a completely randomized design (CRD) with a 4x4 factorial pattern with 5 replications. The study used two factors, namely the concentration of purple sweet potato leaves (0, 2, 4, and 6%) and storage time of milk (0, 4, 8, and 12 days). The variables observed were fat, solid non fat (SNF), total solids, and density. Data were analyzed using variance (ANOVA) and Friedman's test, and significant differences between treatments were further analyzed using Duncan's Multiple Range Test and Dunn's test. The results showed that the addition of purple sweet potato leaf extract concentration had an effect (p<0.05) on SNF, total solids, and density, but had no effect on fat (p>0.05). The storage time of pasteurized goat's milk (p<0.05) had an effect on fat, SNF, total solids, and density. There is an interaction with the concentration and length of storage time in fat. The longer storage time resulted in a decrease in fat, SNF, total solids, and density of pasteurized goat's milk.